Diagnosis and surgical treatment of complicated acute necrotizing pneumonia in children (literature review) - A.F. Halahan (Zdorovʹe Rebenka)
Background. Currently, the problem of diagnosing, treating, and preventing purulent-destructive diseases of the bronchopulmonary system in children remains relevant due to a large number of pulmonary pleural forms and complications of acute necrotizing pneumonia, accompanied by pyofibrinothorax, which leads to adhesion formation in the pleural cavity. The purpose: based on a summary of the available literature, to present the clinical and paraclinical features of pneumonias caused by common pathogens in children and their treatment. The objective of this research is to conduct an analytical review of the literature on the etiopathogenesis, diagnosis, and treatment of this pathology to highlight the main problems in diagnosing and treating children with acute necrotizing pneumonia. Materials and methods. Modern domestic and foreign literary sources on the clinical and paraclinical diagnosis and treatment of destructive pneumonias were reviewed and analysed. The following databases were used for literature search: Web of Science, Scopus, PubMed, and Google Scholar. The results of prospective and retrospective studies conducted in recent years were taken into account when determining recommendations. Results. Current data on acute destructive pneumonia in children are presented. The current state of the problem of early diagnosis and treatment of necrotizing pneumonias is studied. A broader implementation of modern diagnostic methods, particularly ultrasound, and the treatment of acute necrotizing pneumonia in children, both systemically and by affecting the inflammatory focus, are recommended. The treatment of pneumonias in children of different age groups is considered. It was found that establishing the mechanisms of pyofibrinothorax formation could provide an impetus in preventing this complication. The role of fungi in the course of the inflammatory process in the pleural cavity in acute necrotizing pneumonia requires clarification in the experiment. Conclusions. The development of diagnostic and treatment algorithm for children with acute necrotizing pneumonia with pulmonary-pleural complications based on early diagnosis, prevention and treatment using medications and minimally invasive technologies, including thoracoscopy, is relevant.